The Influence of Job Training and Work Experience on the Quality of Waiters in Padang City - Rizal, Wahyu Rahmat; Lise Asnur (Pt. Threeple Herphi Educate, 2025)
The rapid expansion of coffee shops in Padang City has intensified competition, requiring firms to enhance service quality through human capital development. This study investigates the effects of job training and work experience on waiter quality in Padang coffee shops. Using a quantitative causal–associative design, data were collected from 150 respondents selected through purposive sampling, with eligibility criteria including a minimum six-month tenure and direct customer service involvement. A structured questionnaire employing a five-point Likert scale measured job training, work experience, and waiter quality, with validity and reliability confirmed using Pearson correlation and Cronbach’s alpha. Data analysis using multiple linear regression, supported by diagnostic tests for normality, heteroscedasticity, and multicollinearity, revealed that both job training and work experience have positive and significant effects on waiter quality, with work experience exerting a stronger influence. The adjusted R² value of 0.421 indicates that these variables jointly explain 42.1% of the variance in waiter quality, while other factors account for the remaining variance. The findings support human capital theory by demonstrating that structured training improves technical and interpersonal skills, while accumulated experience enhances adaptability, professionalism, and consistency in service delivery. Theoretically, this research contributes to hospitality human resource management literature, and practically, it suggests that managers should prioritize continuous training and provide diverse work exposure to strengthen service quality, improve customer satisfaction, and sustain competitiveness in the coffee shop industry.